2020
DOI: 10.1002/ana.25983
|View full text |Cite
|
Sign up to set email alerts
|

Subtype Diagnosis of Sporadic Creutzfeldt–Jakob Disease with Diffusion Magnetic Resonance Imaging

Abstract: Objective Sporadic Creutzfeldt–Jakob disease (sCJD) comprises several subtypes as defined by genetic and prion protein characteristics, which are associated with distinct clinical and pathological phenotypes. To date, no clinical test can reliably diagnose the subtype. We established two procedures for the antemortem diagnosis of sCJD subtype using diffusion magnetic resonance imaging (MRI). Methods MRI of 1,458 patients referred to the National Prion Disease Pathology Surveillance Center were collected throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 47 publications
(95 reference statements)
1
45
0
Order By: Relevance
“…The original classification of major sCJD subtypes based on histotype and PrP D characteristics has undergone recent revisions [2,11,12,27,32,43]. Sporadic CJDMM(MV)1 (a combination of -MM1 and -MV1, which share histotype and PrP D characteristics) as well as -MM2 (also referred to as MM2C) and -VV2, are seen as definitely distinct subtypes [5,18,19,32]. They are associated with PrP D variants that show distinct conformational and transmissible characteristics but have straightforward electrophoretic profiles of either PrP D type 1 or 2.…”
Section: Discussionmentioning
confidence: 99%
“…The original classification of major sCJD subtypes based on histotype and PrP D characteristics has undergone recent revisions [2,11,12,27,32,43]. Sporadic CJDMM(MV)1 (a combination of -MM1 and -MV1, which share histotype and PrP D characteristics) as well as -MM2 (also referred to as MM2C) and -VV2, are seen as definitely distinct subtypes [5,18,19,32]. They are associated with PrP D variants that show distinct conformational and transmissible characteristics but have straightforward electrophoretic profiles of either PrP D type 1 or 2.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Of note, parietal lobes were abnormal in 96% of patients with sCJDMM2C. 15 The frequency of PSWCs in patients with sCJDMM2C was 44.4%, and the CSF 14-3-3 protein was positive in 62.5% patients. 14 Pathological features of sCJDMM2C include large confluent vacuoles, cerebellar sparing, and PrP Sc perivacuolar deposition.…”
Section: Discussionmentioning
confidence: 98%
“… 5 Striatal and asymmetric lesions are frequently noted in sCJDMM1. 15 PSWCs were detected in 80% cases within 3 months of disease onset. 5 Elevated level of 14-3-3 protein is common in the CSF with 95% being sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Caobelli et al [ 12 ] reported that DWI may be the most sensitive imaging technique for early diagnosis, and MRI in general is the most helpful test for suspected sCJD, as it has excellent specificity and sensitivity[ 13 ]. Repeat brain MRI revealed increased signal intensity in the cortex and head of the left caudate nucleus.…”
Section: Discussionmentioning
confidence: 99%